If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2lnx + -6 = 12 Reorder the terms: -6 + 2lnx = 12 Solving -6 + 2lnx = 12 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 2lnx = 12 + 6 Combine like terms: -6 + 6 = 0 0 + 2lnx = 12 + 6 2lnx = 12 + 6 Combine like terms: 12 + 6 = 18 2lnx = 18 Divide each side by '2nx'. l = 9n-1x-1 Simplifying l = 9n-1x-1
| 3x-20x-7=0 | | x-9+x+5x=180 | | 3=a(3-0)-4 | | -2(7x-4)+6(5x+1)= | | 7x-1-9x+5= | | 4(6x-4)+5(15-3x)-4(2x+3)=-2 | | (x+3)+2x+x=23 | | 3x*3x*3x+4=31 | | 4b+-2a-c= | | 7x-1+9x+5= | | 2j-3=47 | | -18z+6=27z-20 | | y=x^2-10x+106 | | 1+3(m-8)=7-5(6m+6) | | 4+r=6r-3-6r | | 2/5(1-5)x=1/2(4x+3) | | x+1+x+2=180 | | 51-2(11y-12y)= | | f/2=f | | 7z-6=8z-4 | | 3(k-8)=5k | | x+y^2-6y+14=0 | | -13u^2-4=3u^2 | | 5x-8+2(8x+7)= | | 5=6(w-5)-19 | | 1/3v-3/2=-8/5 | | 21=5+2x | | 5(d-4)+6= | | 72=0.6t | | -2x(3y+9)= | | 0=16U^2+4 | | -4y(2y+7z)= |